2009
DOI: 10.1016/j.ijrobp.2008.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Target and Normal Structure Delineation for Breast Cancer Radiotherapy: An RTOG Multi-Institutional and Multiobserver Study

Abstract: Purpose To quantify the multi-institutional and multi-observer variability of target and organ-at-risk (OAR) delineation for breast-cancer radiotherapy (RT), and its dosimetric impacts, as the first step of a RTOG effort to establish a breast cancer atlas. Methods and Materials Nine radiation oncologists specializing in breast RT from eight institutions independently delineated targets (e.g., lumpectomy cavity, boost planning target volume, breast, supraclavicular, axillary and internal mammary nodes, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
209
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(221 citation statements)
references
References 39 publications
9
209
1
2
Order By: Relevance
“…However, even with these techniques, and factoring out variations in contouring, 1 , 2 , 3 , 4 the quality of treatment plans can vary greatly. Nelms et al (5) reported a study where different institutions were asked to produce a plan based on the same downloadable CT dataset with presegmented targets and normal structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with these techniques, and factoring out variations in contouring, 1 , 2 , 3 , 4 the quality of treatment plans can vary greatly. Nelms et al (5) reported a study where different institutions were asked to produce a plan based on the same downloadable CT dataset with presegmented targets and normal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Consistency in delineation is crucial in further development of NTCP models for coronary arteries and in the clinical practice to optimize the RT plan for each patient. Several studies have documented significant inter-observer variation in delineation of target volumes and OARs [16][17][18]. One previously published study on reproducibility of delineating coronary arteries showed a substantial inter-observer variation in estimated dose [19].…”
Section: Introductionmentioning
confidence: 99%
“…The coverage increased to 86%, 71% and 73% with high tangential fields. 51% of level I, 26% of level II and 15% of level III received 95% (V95%) of the dose and this was increased to 79%, 51%, and 49% for high tangents (20). The average dose delivered to level I, II, III by IMRT technique was 80.7%, 69%, 52.3% and by conventional technique it was 85.8%, 67% and 41.8%.…”
Section: Discussionmentioning
confidence: 92%
“…That can have direct correlation, with standard tangents, the axilla receives a significant incidental dose but still adequate for clinical control of disease is unknown [18,19]. Substantial variability was observed in contouring the targets and organ at risk between observers and the structure overlaps were as low as 10% and volume variation had standard variation up to 60% [20]. The average volume of axillary level I, II, III as observed by Julia in 35 patients was 85 cc, 17 cc, 5 cc whereas the mean volume of the axillary level I was 28.9 cc (range 14.5 to 58.6 cc) in a study by Orecchia et al [21] in 15 patients.…”
Section: Discussionmentioning
confidence: 99%